Large eddy simulation of an H-Darrieus rotor. (1st October 2018) - Patil, Rohit; Daróczy, László; Janiga, Gábor; Thévenin, Dominique
Abstract: This study primarily aims to examine the flow field around an H-Darrieus wind turbine using Large Eddy Simulation (LES). The corresponding experimental data for the validation is provided by TU Delft. As in the experiments, the turbine operates at a tip speed ratio (TSR) of 2 and a chord-based Reynolds number (Re) of 8 · 10 4 . A dedicated block-structured mesh has been generated to perform 3D LES simulation by using the WALE subgrid model. The low TSR results in a high angle of attack and causes the turbine to experience dynamic stall, leading to particularly challenging aerodynamic conditions. Normal and tangential forces obtained by LES are compared with experimental results, leading overall to a good agreement. The quality of the LES computation is further confirmed by analyzing turbulent spectra at several locations in the simulations. Finally, vortex shedding from a single turbine blade is studied, revealing that six distinct leading-edge and trailing-edge vortex pairs form and detach during one rotation. Highlights: 3D turbulent flow simulations are performed around an H-Darrieus wind turbine. Large Eddy Simulations (LES) are used with the WALE subgrid-scale model. Normal and tangential forces show good agreement compared with experimental results. Turbulent spectra are analyzed at several locations around the blade. Six distinct leading-edge and trailing-edge vortex pairs are observed during one rotation.